Розробка складу і технології емульгелю для лікування андрогенної алопеції - Ярема, І. О.; Ярема И. А.; Yarema I. O. (Запорізький державний медичний університет, 2021)
Дисертаційна робота присвячена теоретичному й експериментальному обґрунтуванню складу і технології м’якого ЛКЗ з фітосубстанціями капіляропротекторної, венотонічної та фолікулостимулювальної дії для дерматологічного застосування проти АА. На підставі комплексних теоретичних і експериментальних досліджень опрацьовано раціональний склад і технологію емульгелю під умовною назвою «Флавостерол», що містить ПСЕС і СЯН для профілактики та лікування АА. За результатами проведених випробувань отримано патент України на корисну модель «Косметичний засіб для корекції андрогенної алопеції» (реєстраційний № 115179 від 10.04.2017 р.). Екстемпоральну технологію емульгелю викладено в інформаційному листі та запроваджено в практику виробничих аптек м. Івано-Франківська. Розроблено технологічну інструкцію на виробництво ЛКЗ «Флавостерол-емульгель». Технологію виготовлення апробовано в умовах дрібносерійного виробництва аптеки № 6 «Леда», м. Харків (акт апробації від 17.02.2020 р.). Окремі фрагменти роботи упроваджено в науково-педагогічний процес фармацевтичних і медичних закладів вищої освіти України. Диссертация посвящена теоретическому и экспериментальному обоснованию состава и технологии мягкого лекарственного косметического средства с фитосубстанциямы капилляропротекторного, венотонического и фолликулостимулирующего действия для дерматологического применения против АА. На основании комплексных теоретических и экспериментальных исследований разработаны рациональный состав и технология эмульгеля под условным названием «Флавостерол», содержащего пальмы Сабаль экстракт сухой и софоры японской настойку для профилактики и лечения АА. По результатам проведенных испытаний получен патент Украины на полезную модель «Косметическое средство для коррекции андрогенной алопеции» (регистрационный № 115179 от 10.04.2017 г.). Экстемпоральную технологию эмульгеля изложено в информационном письме и внедрено в практику производственных аптек г. Ивано-Франковска. Разработано технологическую инструкцию на производство ЛКС «Флавостерол-эмульгель». Технология изготовления апробирована в условиях мелкосерийного производства аптеки № 6 «Леда», г. Харьков (акт апробации от 17.02.2020 г.). Отдельные фрагменты работы внедрены в научно-педагогический процесс фармацевтических и медицинских высших учебных заведений Украины. The dissertation is dedicated to the theoretical and experimental substantiation of structure and technology of medical cosmetic remedy (MCR) in the form of an emulgel with the Serenoa repens dry extract (SRDE) and Sophora japonica tincture (SJT), intended for use in trichology, namely for the prevention and treatment of androgenic alopecia (AA). An analysis of the literature and summarized data on the AA etiology and pathogenesis were carried out. The main differences between the clinical manifestations of AA in men and women were clarified. It has been found that the use of active pharmaceutical ingredients of synthetic origin such as minoxidil and finasteride, despite their proven efficiency in the AA treatment, have a large number of local and systemic side effects. Medical cosmetic remedies of plant origin with a high content of phytosterols and flavonoids are the alternative to the synthetic drugs. A marketing analysis of the domestic pharmaceutical market of medicines, dermatocosmetics and dietary supplements against AA was carried out. It was confirmed that the number of domestically produced drugs and dermatocosmetics / dietary supplements was significantly lower than the imported products. It was found that there were no drugs in the soft dosage forms for cutaneous application against AA. The sociological studies about the AA problems in 150 men were carried out. It was proved that for the vast majority of respondents (48.7%) solving their AA problems was important. Almost 30.0 % of them agreed that the drug effectiveness for the AA treatment was more important than its price. Based on the obtained data it has been established that the MCR development in the soft dosage form as the emulgel with SRDE and SJT against AA is promising. Taking into account the results of the complex experimental studies, the final formulation of emulgel «Flavosterol» was developed, namely: SRDE – 3.0 g, SJT – 7.0 g, oil pumpkin seeds – 5.0 g, cetyl alcohol – 3.0 g, polysorbate 20 – 3.0 g, carbopol Ultrez 10 – 0.3 g, triethanolamine – 0.2 g, potassium sorbate – 0.1 g, salicylic acid – 0.1 g, utylhydroxytoluene – 0.02 g, lavender essential oil – 0.2 g, purified water – up to 100.0 g. On the basis of pharmacotechnological research the technological parameters of the emulgel production were defined, namely: temperature mode – 60 °С, emulsification with alternate introduction of oil and water phases to a mixture of emulsifiers, homogenization during 30 min at a speed of 2000 rpm. Taking into account the investigation results the emulgeloptimal technology in compounding pharmacy and industrial conditions was substantiated. The technology of the emulgel was described in the Information Letter «Technology of manufacturing a combined herbal preparation «Flavosterol-emulgel» for local treatment of androgenic alopecia in pharmacies» and was tested in pharmacies with extemporaneous drug compounding. The project of the Technological Instruction for production of MCR «Flavosterol-emulgel» was developed. The manufacturing technology was tested in the conditions of small-scale production of the compounding pharmacy № 6 «Leda», Kharkiv (approbation act dated 17.02.2020). The emulgel quality control was carried out according to the following indicators: organoleptic (colour, odour, homogeneity), physical and chemical (identification and quantification of biologically active substances, rheological parameters, colloidal and thermal stability, pH), microbiological (microbiological purity). On the basis of the received data the Project of the methods of the emulgel quality control was developed and the optimum temperature mode of the MCR storage and shelf life was established, namely 2 years at a temperature of 25 ± 2 °C. On the models of symptomatic and androgenic alopecia in rats, the folliclestimulating and vasodilating activity of the emulgel «Flavosterol» was proven. On the model of Parametium caudatum microorganisms the emulgel membrane-protective properties were established. According to the study results of acute toxicity, sensitizing and local irritating effects on laboratory animals, it was found that the developed emulgel did not exhibit harmful effects when applied cutaneously and can be rated as Vth class of practically non-toxic substances. According to the experimental results, a Patent of Ukraine was obtained for the utility model «Cosmetic for the correction of androgenic alopecia» (registration № 115179 dated 10.04.2017). The research results were included to the educational process of higher education institutions of pharmaceutical (medical) profile of Ukraine.
Разработка состава и технологии эмульгеля для лечения андрогенной алопеции
Development of emulgel composition and technology for the androgenic alopecia treatment
Keywords: трихологія; андрогенна алопеція; технологія; лікарські косметичні засоби; емульгель; активні фармацевтичні інгредієнти; пальми Сабаль екстракт сухий; софори японської настойка; трихология; андрогенная алопеция; технология; лекарственные косметические средства; эмульгель; активные фармацевтические ингредиенты; пальмы Сабаль экстракт сухой; софоры японской настойка; trichology; androgenic alopecia; technology; medical cosmetic remedies; emulgel; active pharmaceutical ingredients; Serenoa repens dry extract; Sophora japonica tincture